6 Does Bedding Influence Lying Behaviour of Cattle Unloaded for Rest During Long-distance Transportation?. (8th October 2021) - Guzman, Paula Olivares; Pearl, David L; Schwartzkopf-Genswein, Karen S; Widowski, Tina M; Meléndez Suárez, Daniela M; Marti, Sonia; Haley, Derek B
Abstract: In Canada, cattle must be unloaded, fed, watered, and rested after 36 h of transport; however, little is known about what constitutes appropriate rest station conditions. The objective of this study was to determine the relationship between providing straw bedding (14-cm deep) and trip, load, and commercial rest station characteristics, on lying behaviour. Truckloads (n = 13) were split; half the animals were assigned to either bedded (n = 452 cattle) or non-bedded (n = 470 cattle) pens. Trip characteristics [time in motion (TIM), duration of stops en route (DUR_STOPS)], load characteristics (sex: heifers, steers, both; and load weight), and rest station characteristics [ambient temperature at unloading; rest pen space allowance (k_PEN); time in resting pen (TIP)] were recorded. Once unloaded we counted the number of cattle lying/pen, every 10 min for 8 h. A mixed logistic regression model with random intercepts for load and truck compartment was fitted to examine associations between the proportion of animals lying and the independent variables (i.e., treatment, trip, load, and rest station characteristics). Odds of lying increased with load weight (i.e., cattle weight class, P = 0.02) and with DUR_STOPS (P < 0.03). There was an interaction (P < 0.01) between treatment and TIM: as TIM increased, the odds of observing cattle lying showed a notable increase for cattle rested in bedded pens, whereas for those rested in non-bedded pens, the odds showed little change as TIM increased. An interaction (P < 0.01) was also found between treatment and TIP: early in the observation period, the odds of cattle lying were greater in bedded pens. Both groups showed an increase in the probability of lying over time, plateauing at similar levels, near the end of the 8-h observation period. In conclusion, providing straw bedding at rest stations influenced cattle's motivation to lie, particularly following longer transport durations.